2021
DOI: 10.1155/2021/8340925
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning Based Straggler Prevention in Large-Scale Distributed Computing Framework

Abstract: Modern big data applications tend to prefer a cluster computing approach as they are linked to the distributed computing framework that serves users jobs as per demand. It performs rapid processing of tasks by subdividing them into tasks that execute in parallel. Because of the complex environment, hardware and software issues, tasks might run slowly leading to delayed job completion, and such phenomena are also known as stragglers. The performance improvement of distributed computing framework is a bottleneck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…However, in the actual decision-making process, due to the ambiguity of decision-making information and the limitations of decision-makers cognition, decision-makers are often more willing to give evaluation information in the form of interval language to reduce decision-making pressure. In response to such problems, [ 11 ] showed the definition of interval binary semantics and several set counters and used the interval binary semantic possibility formula to sort the solutions; reference [ 12 ], based on the maximum dispersion [ 13 ], defined a new interval binary semantic Bonferroni average operator and its corresponding weighting method; reference [ 14 ] combined interval binary semantics and VIKOR method, and proposed an outsourcing supplier selection method; reference [ 15 ] proposed a subway door failure risk assessment method based on interval binary semantics and failure mode. The method proposed in the literature [ 11 15 ] has the following shortcomings: first, the evaluation information is uniformly distributed in the interval by default, and the distribution of information in the gap that is more in line with the psychology of decision-makers is not considered; second, most of the existing research in the single static stage, [ 16 ] it is not suitable for the situation that requires dynamic multistage analysis; thirdly, the above methods all assume that the decision-maker is entirely rational, [ 17 ] but in the actual decision-making, the decision-makers psychological behavior is often bounded rationality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the actual decision-making process, due to the ambiguity of decision-making information and the limitations of decision-makers cognition, decision-makers are often more willing to give evaluation information in the form of interval language to reduce decision-making pressure. In response to such problems, [ 11 ] showed the definition of interval binary semantics and several set counters and used the interval binary semantic possibility formula to sort the solutions; reference [ 12 ], based on the maximum dispersion [ 13 ], defined a new interval binary semantic Bonferroni average operator and its corresponding weighting method; reference [ 14 ] combined interval binary semantics and VIKOR method, and proposed an outsourcing supplier selection method; reference [ 15 ] proposed a subway door failure risk assessment method based on interval binary semantics and failure mode. The method proposed in the literature [ 11 15 ] has the following shortcomings: first, the evaluation information is uniformly distributed in the interval by default, and the distribution of information in the gap that is more in line with the psychology of decision-makers is not considered; second, most of the existing research in the single static stage, [ 16 ] it is not suitable for the situation that requires dynamic multistage analysis; thirdly, the above methods all assume that the decision-maker is entirely rational, [ 17 ] but in the actual decision-making, the decision-makers psychological behavior is often bounded rationality.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent experiments, they found that the subjects' psychological-expression recognition ability was positively correlated with lie recognition ability [ 13 ]. Afterwards, the Japanese and Caucasian Brief Affect Recognition Test (JACBART) [ 14 , 15 ] was conducted, verifying that the subjects' psychological-expression recognition ability was positively correlated with lie recognition ability [ 20 ], it can be proved that psychological-expressions can effectively help people identify lies. Face psychological expression recognition involves image processing and analysis, computer vision, artificial intelligence, psychology, biology, and other directions.…”
Section: Introductionmentioning
confidence: 99%
“…The output nodes of the algorithm model were normal and abnormal respectively. 13,817 pieces of data were collected in the industrial control experiment, among which 9817 pieces of data were taken as the test data set, including 9770 pieces of normal data and 47 pieces of abnormal data [21][22]. In addition, 4000 of them as test data sets contain 3987 normal data and 13 abnormal data.…”
Section: Industrial Control Simulation Testmentioning
confidence: 99%
“…• HEF: HEF is an enhancement technique that employs a Gaussian filter to enhance the edges in the input image (Bundy and Wallen 1984). The edges emerge presented in the high-frequency variety as they have more shifts that are dramatic in intensity (Deshmukh et al 2021). This enhancement technique generates a low contrastenhanced image and implements the Histogram Equalization method to improve contrast and sharpness.…”
Section: Image Enhancement Techniquesmentioning
confidence: 99%